Efektivitas Model Pembelajaran Disaster Nutrition Community-Based Learning (DNCBL) dalam Meningkatkan Pemahaman Mahasiswa Kedokteran tentang Manajemen Gizi Bencana: Studi Kuasi-Eksperimental - Putra Nagaring, Sulaiman; Yusuf, Zuhriana K; Nuryana, Riska; Mulyadi, Jesica; Lahay, Sitty Fadhilla Fitrianty (Universitas Muhammadiyah Magelang, 2026)
Abstract Introduction: Disaster nutrition management is an important competency for medical students, particularly in disaster-prone areas where vulnerable groups are at risk of nutritional problems due to limited access to food and health services. The Disaster Nutrition Community-Based Learning (DNCBL) model was developed as an educational innovation that integrates disaster nutrition concepts, community-based learning, case discussion, and contextual problem solving. Objective: This study aimed to evaluate the effectiveness of the DNCBL model in improving medical students’ understanding of disaster nutrition management. Methods: This study used a quasi-experimental design with a one-group pretest–posttest approach. The study was conducted among medical students at the Faculty of Medicine, Universitas Negeri Gorontalo, in the 2025/2026 academic year. Data were collected using pre-test and post-test instruments and analyzed descriptively and inferentially using a paired sample t-test. Results: The mean score increased from 14.20 ± 1.166 before the intervention to 14.79 ± 0.581 after the intervention. The number of students achieving the maximum score increased from 35 students (57.4%) to 52 students (85.2%). The paired sample t-test showed a significant difference between pre-test and post-test scores (p = 0.000). Conclusion: The DNCBL model was effective in improving medical students’ understanding of disaster nutrition management and may serve as an innovative learning approach in disaster-related medical education.